Till Stratigraphy and Late Wisconsinan Deglaciation of Southern Maine: A Review - Thompson, Woodrow; Borns Jr., Harold (Géographie physique et Quaternaire)

(untitled) (Les Presses de l'Université de Montréal, 1985)
ABSTRACTAt least two glaciations are recorded by the till stratigraphy of southern Maine. A more deeply weathered lower till is tentatively correlated with the early Wisconsinan (or older) Nash Stream Till in New Hampshire and its inferred equivalents in southern New England and Québec. The Laurentide Ice Sheet flowed south-southeastward across southern Maine in late Wisconsinan time and deposited the upper till. By about 14,000 years ago the ice sheet started to recede from the Maine coast, and the high peaks of the Mahoosuc Range emerged as nunataks in western Maine. Marine transgression accompanied déglaciation of lowland areas of southern Maine, with deposition of end moraines, deltas, and subaqueous outwash along the active ice margin, while thick clay deposits of the Presumpscot Formation accumulated on the ocean floor. The ice margin retreated quickly, reaching the marine limit in central Maine by 13,000 yr BP. The Pineo Ridge moraine system in eastern Maine, formerly thought to represent a major readvance, is reinterpreted as a glacial stillstand near the marine limit. Deglaciation inland from the marine limit in eastern and southwestern Maine occurred by recession of an active ice margin in some areas, and elsewhere by stagnation and downwasting of ice that was separated from the active ice sheet. Southern Maine was ice-free by 12,000 yr BP. but marine submergence persisted until about 11,000 years ago in the southwestern coastal lowland.